Brain Tumors - An Update 2018
DOI: 10.5772/intechopen.78578
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Intrinsic Pontine Glioma

Abstract: Diffuse intrinsic pontine glioma (DIPG) is a leading cause of brain cancer-related death in children. These aggressive high-grade gliomas cannot be effectively treated and are associated with dismal prognosis. Whilst radiation therapy (RT) prolongs survival, it is a palliative therapy, as half of children with DIPG die within 1 year of diagnosis and almost all are dead by 2 years. These statistics have not changed for decades, despite a multitude of clinical trials. No chemotherapeutic regimen has been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 192 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Although in a survival prediction model, DIPG spread to the medulla and midbrain was not a significant prognostic value (3), in a different study extrapontine extension was shown to be more common in short-term compared to longterm survivors (2). This impact on DIPG prognosis can be due to the ability of invading DIPG cells to distort, displace, and destroy nerve fiber tracts (4). For instance, specific symptoms like impairment of gait, coordination, and speech, are thought to be associated with invasion of tumor cells to the adjacent cerebellum (5).…”
Section: Introductionmentioning
confidence: 98%
“…Although in a survival prediction model, DIPG spread to the medulla and midbrain was not a significant prognostic value (3), in a different study extrapontine extension was shown to be more common in short-term compared to longterm survivors (2). This impact on DIPG prognosis can be due to the ability of invading DIPG cells to distort, displace, and destroy nerve fiber tracts (4). For instance, specific symptoms like impairment of gait, coordination, and speech, are thought to be associated with invasion of tumor cells to the adjacent cerebellum (5).…”
Section: Introductionmentioning
confidence: 98%
“…In this subsection, we will focus primarily on DMGs: they are of particular interest for immunotherapy development given their dismal responses to existing treatments. Approximately 70-80% of DMGs are primarily driven by epigenetic mis-regulation, wherein mutations to the H3 histone-most often a lysine to methionine mutation (K27M)-disrupt the packaging of replicated DNA and its integration into transcriptionally active regions of the genome [143,144]. Because of their highly diffuse, invasive, and pernicious growth that distorts local brain tissue, the available knowledge on the TIME relies heavily on autopsy samples, and more limited data are available on the nature of the DMG TIME at earlier pathophysiological stages and prior to treatment [145].…”
Section: High-grade Pediatric Gliomasmentioning
confidence: 99%
“…DMG is known for its aggressive nature, dismal outcomes, and poor prognosis with a 99% 5-year mortality rate [ 13 ]. Due to the high morbidity associated with surgery in such an eloquent region of the brain and sampling errors associated with biopsies, the treatment options for DMG are confined to either chemotherapy, radiotherapy, or targeted molecular agents, all of which are associated with minimal effectiveness [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%